2018
DOI: 10.1021/acsami.7b18140
|View full text |Cite
|
Sign up to set email alerts
|

Finely Tuned SnO2 Nanoparticles for Efficient Detection of Reducing and Oxidizing Gases: The Influence of Alkali Metal Cation on Gas-Sensing Properties

Abstract: Tin dioxide (SnO2) nanoparticles were straightforwardly synthesized using an easily scaled-up liquid route that involves the hydrothermal treatment, either under acidic or basic conditions, of a commercial tin dioxide particle suspension including potassium counterions. After further thermal post-treatment, the nanomaterials have been thoroughly characterized by Fourier transform infrared and Raman spectroscopy, powder X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 80 publications
0
37
0
Order By: Relevance
“…The response recovery times were calculated as the time intervals between the time at which the response has achieved 90% of its maximum and the time at which it has decreased to 10% of its maximum. 12…”
Section: Methodsmentioning
confidence: 99%
“…The response recovery times were calculated as the time intervals between the time at which the response has achieved 90% of its maximum and the time at which it has decreased to 10% of its maximum. 12…”
Section: Methodsmentioning
confidence: 99%
“…Other remarkable responses have been reported for different nanoparticle networks with no hierarchical organization [16,40,55,86]. Visually extrapolating the calibration curves of the reported materials allows to compare layers tested in different concentration ranges.…”
Section: Response Amplitude and Calibration Curvementioning
confidence: 62%
“…The band diagram in the two regimes is schematically reported in Figure 2. Schematic representation of the energy band diagram in a spherical grain of diameter t in the regional depletion regime (a), in which the grain diameter is larger than two times the depletion layer W (t > 2W), and in the volume depletion regime (b), in which 2W > t. Adapted with permission from [40]. Copyright (2018) American Chemical Society.…”
Section: Crystallite Size Effectsmentioning
confidence: 99%
“…prepared finely tuned SnO 2 nanoparticles and studied the influence of alkali metal cation (potassium residuals) on gas sensing properties. [ 81 ] They found that the surface area and Debye length of SnO 2 are not dominant factors in gas sensitivity. SnO 2 samples that were synthesized under acidic conditions and calcined in air obtained the best sensing performances because of a lower amount of potassium residuals and higher crystallinity.…”
Section: Materials For Gas Sensingmentioning
confidence: 99%